Perceived usefulness and confirmation on continuance intention of Shopee application users - Laura Yuliantika; Astra Prima Budiarti (Universitas Negeri Padang, 2023)
E-commerce is becoming increasingly common in a variety of industrialized and developing nations, including Indonesia. After the acceptance phase has been successful, it is important to learn more about the user's intention to continue utilizing e-commerce alternatives. The goal of this study is to examine the influences of perceived usefulness and confirmation on users of the Shopee application's intention to continue using it in Padang City. All Padang City Shopee application users made up the study's sample. There are 200 respondents in the research sample. An online questionnaire was used to collect data, and state-of-the-art PLS (Partial Least Square) software was used to process the data. The results of the data analysis reveal the following: (1) Perceived Usefulness has a significant effect on the satisfaction of Shopee application users. (2) Confirmation has a significant effect on the satisfaction of Shopee application users. (3) Satisfaction has a significant effect on the continuance intention of Shopee application users. (4) Perceived Usefulness has a significant effect on the continuance intention of Shopee application users mediated by satisfaction. (5) Confirmation has a big impact on users of the Shopee application's intention to continue using it, via satisfaction.